2002
DOI: 10.1159/000064525
|View full text |Cite
|
Sign up to set email alerts
|

Increased Angiotensin II AT<sub>1</sub> Receptor Expression in Paraventricular Nucleus and Hypothalamic-Pituitary-Adrenal Axis Stimulation in AT<sub>2</sub> Receptor Gene Disrupted Mice

Abstract: Angiotensin II AT2 receptor gene-disrupted mice have increased blood pressure and response to angiotensin II, behavioral alterations, greater response to stress, and increased adrenal AT1 receptors. We studied hypothalamic AT1 receptor binding and mRNA by receptor autoradiography and in situ hybridization, adrenal catecholamines by HPLC, adrenal tyrosine hydroxylase mRNA by in situ hybridization and pituitary and adrenal hormones by RIA in AT2 receptor-gene disrupted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 32 publications
5
35
0
1
Order By: Relevance
“…In addition, it is apparent that there is a reciprocal regulation between receptor subtypes (46,49), and the direction of the regulation depends on both the cell type and the hormonal milieu to which it is exposed. In several tissues, there is cross talk between AT1 and AT2 receptors, and the expression of AT1 receptors can be dependent on AT2 receptor expression (3,46). Furthermore, a direct, positive effect of estrogens on the density of AT2 receptors has been demonstrated in the human myometrium (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is apparent that there is a reciprocal regulation between receptor subtypes (46,49), and the direction of the regulation depends on both the cell type and the hormonal milieu to which it is exposed. In several tissues, there is cross talk between AT1 and AT2 receptors, and the expression of AT1 receptors can be dependent on AT2 receptor expression (3,46). Furthermore, a direct, positive effect of estrogens on the density of AT2 receptors has been demonstrated in the human myometrium (33).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that estrogen modifies AT2 expression in the myometrium (33). Moreover, both receptors can mutually influence their gene expression profiles (3). Therefore, in view of the observed estrogen-induced downregulation of AT1 receptors in anterior pituitary, we set out to determine whether in vivo estrogen treatment modified the expression and function of AT2 receptors in this tissue.…”
mentioning
confidence: 99%
“…This report is based on the finding of enhanced neurological deficits in AT 2 receptor knockout mice following middle cerebral artery occlusion. The authors did not consider that failure of AT 2 receptor transmission results in enhanced brain AT 1 receptor expression (Armando et al, 2002), a finding which can explain the increased sensitivity of AT 2 receptor knockout mice to ischemia. In addition, blockade of Ang II synthesis with ACE inhibitors should result in a decrease in both AT 1 and AT 2 receptor stimulation.…”
Section: The Role Of At Receptorsmentioning
confidence: 99%
“…The feedback between AT 1 /AT 2 receptors have been confirmed in AT 2 receptor knockout mice, where absence of AT 2 receptors correlates with increased AT 1 receptor binding and mRNA in hypothalamus, adrenal gland and kidney. [27][28][29] The hypothesis of AT 1 /AT 2 receptor cross-talk including activation of phosphatases by AT 2 receptor stimulation suppressing mitogen-activated protein kinase activation and counteracting AT 1 receptor effects 30 assumed same cell localization of both receptors. However, we have found that in cerebral microvessels, whereas AT 1 receptors colocalize with endothelial markers indicating an endothelial localization, AT 2 receptors do not.…”
Section: Zhou Et Al At 1 Blocker and Brain Microvascular Ang II Systemmentioning
confidence: 99%